Self-Perception of Ukrainian Refugee Women in Germany: An Empirical Study - Repkina, Nataliia; Rach, Olga (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
This article presents the results of an empirical study of the psychological characteristics of self-perception and self-esteem among Ukrainian refugee women who were forced to relocate to Germany after the full-scale Russian invasion. The relevance of the study is determined by the need to understand how the loss of pre-war social status, professional identity and habitual social roles affects the integrity of the self-image and psychological well-being of women in a new sociocultural environment. The aim of the study was to identify the relationships between self-perception, global self-esteem, level of aspirations, pre-war social status, current employment status in Germany, and indicators of psychological well-being. The sample consisted of 50 Ukrainian women aged 25–45 who had been living in Germany for at least 12 months. Data were collected using a modified Dembo–Rubinstein scale (indices Δ Loss and Δ Expectation), a self-esteem scale (Ryff modification), a self-perception questionnaire based on the client-centred approach of C. Rogers in O. Diamond’s adaptation, and the Psychological Well-Being Scale by C. Ryff, supplemented by socio-demographic variables (pre-war status, employment). The results showed that most respondents demonstrate moderate to high levels of perceived loss, with the highest Δ Loss found among women who had high pre-war social status and are currently unemployed. These women are characterised by a more fragmented self-image, decreased self-acceptance and lower scores on autonomy and environmental mastery, while dimensions such as personal growth and purpose in life remain relatively preserved. Correlation analysis revealed significant negative links between Δ Loss and self-esteem (r = –0.56), self-perception (r = –0.62) and overall psychological well-being (r = –0.48), as well as between Δ Expectation and self-perception (r = –0.41). Pre-war social status positively correlates with Δ Loss (r = +0.52) and negatively with self-perception, indicating deeper experiences of loss and difficulty integrating the previous self-image into the new reality. Employed women show higher levels of self-esteem, self-acceptance, autonomy and environmental mastery, together with lower Δ Loss scores, compared to unemployed participants. The findings underscore the role of self-perception as a key personal resource for adaptation and highlight the risk of a “stabilised dependence” on social benefits in part of the high-status group. The results have theoretical and practical implications for the development of psychological support programmes for refugee women that combine work with the self-image, reconstruction of meaning and realistic life goals with support for employment and professional self-realisation as important protective factors.